2023
DOI: 10.1364/boe.485999
|View full text |Cite
|
Sign up to set email alerts
|

Automated segmentation and quantification of calcified drusen in 3D swept source OCT imaging

Abstract: Qualitative and quantitative assessments of calcified drusen are clinically important for determining the risk of disease progression in age-related macular degeneration (AMD). This paper reports the development of an automated algorithm to segment and quantify calcified drusen on swept-source optical coherence tomography (SS-OCT) images. The algorithm leverages the higher scattering property of calcified drusen compared with soft drusen. Calcified drusen have a higher optical attenuation coefficient (OAC), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the same study, we demonstrated that reduced flow signal was not confined to areas under drusen and that the mean difference in FD% when including drusen vs excluding drusen was negligible. Drusen, especially if calcified, may reduce FD% detectability, 62 , 63 a pertinent concern for AMD eyes at more severe stages of intermediate AMD than those included in ALSTAR2.…”
Section: Methodsmentioning
confidence: 99%
“…In the same study, we demonstrated that reduced flow signal was not confined to areas under drusen and that the mean difference in FD% when including drusen vs excluding drusen was negligible. Drusen, especially if calcified, may reduce FD% detectability, 62 , 63 a pertinent concern for AMD eyes at more severe stages of intermediate AMD than those included in ALSTAR2.…”
Section: Methodsmentioning
confidence: 99%
“…The development of sophisticated image processing algorithms has enhanced the accuracy of automatic RPE-drusen complex calculations [100][101][102]. The automated quantification of drusen as well as other retinal abnormalities is useful in monitoring AMD progression.…”
Section: Oct Evaluation Of Drusenmentioning
confidence: 99%
“…31 , 32 Consequently, the calcified deposits impede the OCT light from penetrating into the choroid, resulting in hypoTDs in the choroidal layer. 29 This process is similar to the one caused by increased pigmentation within the retina, known as hyperreflective foci, or along the RPE border. 9 , 33 However, although we observed complete hypoTDs in the CC layer and deeper choroidal layers beneath hyperpigmentation, CaD resulted in a complete hypoTD specifically within the deeper choroidal layers (e.g., subRPE slab) but not in the CC layer.…”
mentioning
confidence: 91%
“…The presence of CaD, also known as refractile drusen on color fundus imaging or drusen with either hyperreflective or hyporeflective cores on OCT imaging, has been shown to be a biomarker for disease progression. [28][29][30] CaD contain calcium phosphate spherules, 6 leading to increased optical absorption and light scattering. 31,32 Consequently, the calcified deposits impede the OCT light from penetrating into the choroid, resulting in hypoTDs in the choroidal layer.…”
mentioning
confidence: 99%